(√(2 2/5) - √(5 2/5)) : √(3/20) = (√(12/5) - √(27/5)) : √(3/20) = √(12/5 : 3/20) - √(27/5 : 3/20) = √(12•20/5•3) - √(27•20/5•3) = √(4•4/1•1) - √(9•4/1•1) = √16 - √(9•4) = 4 - 3•2 = -2.
крч ответ -2
Ответ: \frac{ \sqrt{ 2\frac{2}{5}}- \sqrt{ 5\frac{2}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{ \sqrt{ \frac{12}{5}}- \sqrt{ \frac{27}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{ \sqrt{ \frac{4*3}{5}}- \sqrt{ \frac{9*3}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{2 \sqrt{ \frac{3}{5}}- 3\sqrt{ \frac{3}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{-\sqrt{ \frac{3}{5}} }{ \sqrt{ \frac{3}{2} } } =
- \sqrt{ \frac{3*2}{5*3} } =- \sqrt{ \frac{2}{5} }
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(√(2 2/5) - √(5 2/5)) : √(3/20) = (√(12/5) - √(27/5)) : √(3/20) = √(12/5 : 3/20) - √(27/5 : 3/20) = √(12•20/5•3) - √(27•20/5•3) = √(4•4/1•1) - √(9•4/1•1) = √16 - √(9•4) = 4 - 3•2 = -2.
крч ответ -2
Ответ: \frac{ \sqrt{ 2\frac{2}{5}}- \sqrt{ 5\frac{2}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{ \sqrt{ \frac{12}{5}}- \sqrt{ \frac{27}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{ \sqrt{ \frac{4*3}{5}}- \sqrt{ \frac{9*3}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{2 \sqrt{ \frac{3}{5}}- 3\sqrt{ \frac{3}{5} } }{ \sqrt{ \frac{3}{2} } } =
\frac{-\sqrt{ \frac{3}{5}} }{ \sqrt{ \frac{3}{2} } } =
- \sqrt{ \frac{3*2}{5*3} } =- \sqrt{ \frac{2}{5} }
Пошаговое объяснение: